Improvement of paperboard moisture resistance by coating with lignin using the rapid expansion of subcritical solutions process - Kongsakorn, Suwit; Amporn Sane (Agriculture and Natural Resources, 2021)
The rapid expansion of subcritical solutions (RESS) process was successfully carried out to coat paperboard with lignin to improve its moisture barrier property. This work focused on systematic study of effects of the RESS conditions—lignin concentration, pre-expansion temperature and pressure (Tpre, Ppre, respectively)—on the surface morphology, surface roughness and moisture barrier properties of lignin-coated paperboard. Fourier transform-infrared spectroscopic analysis was performed to ensure the presence of the lignin coating layer on the substrate surface. Typically, the coating layer on the paperboard surface consisted of submicron lignin particles and thin films. The presence of discrete submicron particles decreased when the concentration of lignin was reduced from 0.50% to 0.25% and when the pre-expansion temperature was increased from 80°C to 100°C. The air leakage and water vapor transmission rates of lignin-coated paperboard were primarily controlled by the presence of the uniform coating layer and the thin film of lignin, respectively. The moisture barrier property of paperboard increased after coating with lignin. Among the tested operating conditions, the RESS coating of 0.50% lignin solution at Tpre = 100°C and Ppre = 13.8 MPa effectively provided a smoother and more uniform continuous coating layer on the paperboard surface with up to 20% improved moisture resistance.